Síndrome burnout y su relación con la inteligencia emocional de los servidores públicos del GAD Municipal del cantón Junín año 2022 - Avellán Bravo, Fabiana Milena (2023)
The objective of this investigation was to analyze the relationship between Burnout Syndrome (SB) and Emotional Intelligence (EI) in public servants of the Municipal GAD of Cantón Junín for the improvement of work performance in the period 2022. For the diagnosis of level of Burnout syndrome and emotional intelligence in the public servants of the Municipal GAD of Junín, two surveys were applied to 76 officials sheltered under the Labor Code, the first Maslach Burnout Inventory questionnaire, which through 22 items evaluates professional burnout, on the other hand, emotional intelligence was examined using the BARON ICE Test, which recognizes the emotional aptitudes of personality. However, strategies were designed as a proposal to combat the levels of Burnout Syndrome as the main problem. The results showed that the civil servants present a considerable percentage of SB, while in IE there were medium and high values, thus establishing a relationship between the dimensions of the burnout syndrome and the components of emotional intelligence as inversely proportional, that is to say that by having a greater Burnout degree, Emotional Intelligence is medium to low in certain components and by increasing EI values, Burnout levels decrease in low to medium percentages. With the problem presented, the design of strategies that allow the collaborators of the institution to strengthen their Emotional Intelligence through strategies and programs to avoid considerable levels of stress is recommended.